2021
DOI: 10.1093/cz/zoab039
|View full text |Cite
|
Sign up to set email alerts
|

Viability, behavior, and color expression in the offspring of matings between common wall lizard Podarcis muralis color morphs

Abstract: Colour polymorphisms are widely studied to identify the mechanisms responsible for the origin and maintenance of phenotypic variability in nature. Two of the mechanisms of balancing selection currently thought to explain the long-term persistence of polymorphisms are the evolution of alternative phenotypic optima through correlational selection on suites of traits including colour, and heterosis. Both of these mechanisms can generate differences in offspring viability and fitness arising from different morph c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 126 publications
(207 reference statements)
1
9
0
Order By: Relevance
“…Similarly, a recent study indicated that locality is a better predictor of genetic differentiation than colour morph in P. muralis (Andrade et al, 2019). Furthermore, our results are congruent with recent work from Abalos et al (2022) arguing against reduced viability of hatchlings (i.e., post-zygotic barriers) from colour-disassortative matings, which could arise under strong correlational selection and assortative mating (Gray & McKinnon, 2007;Lancaster et al, 2014;Sinervo & Svensson, 2002). However, our results are in contrast with the previous behavioural (Pérez i de Lanuza et al, 2013Lanuza et al, , 2016 and genetic (Bellati, 2011) studies, which suggested some degree of assortative mating in this species.…”
Section: Population Analysessupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, a recent study indicated that locality is a better predictor of genetic differentiation than colour morph in P. muralis (Andrade et al, 2019). Furthermore, our results are congruent with recent work from Abalos et al (2022) arguing against reduced viability of hatchlings (i.e., post-zygotic barriers) from colour-disassortative matings, which could arise under strong correlational selection and assortative mating (Gray & McKinnon, 2007;Lancaster et al, 2014;Sinervo & Svensson, 2002). However, our results are in contrast with the previous behavioural (Pérez i de Lanuza et al, 2013Lanuza et al, , 2016 and genetic (Bellati, 2011) studies, which suggested some degree of assortative mating in this species.…”
Section: Population Analysessupporting
confidence: 93%
“…Finally, colour alleles may counterbalance the build-up of population structure by acting as genomic bridges between morphs (Comeault et al, 2015). In fact, white individuals can carry orange (o) and yellow alleles (y) in heterozygosity, while orange lizards can present every genotype at the yellow locus (YY, Yy or yy); thus, offspring of P. muralis will not always express the same phenotype as their parents (Abalos et al, 2022;Aguilar et al, 2022;Andrade et al, 2019). Mosaic morphs (i.e., whiteorange and yellow-orange) may also facilitate gene flow between colour morphs, but further work is needed to understand their basis and role in the maintenance of colour morphs of P. muralis.…”
Section: Genomic Differentiation Between Individuals Analysed In Thismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in natural sympatric populations in the Pyrenees, no differences were found between morphs in terms of site fidelity, territory size or spatial overlap of males and females [78]. Similarly, colour morph was irrelevant to sociosexual behaviour, habitat, and reproductive success [78,79]. Any ecomorphological trait (head, limbs, boot) that improves reproductive success could also be used to escape from predators or capture prey, so one would expect differences in ecological traits among morphs to be reflected in their morphology and performance traits.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Pérez i de Lanuza & Carretero 2018; but see Abalos et al . 2020, 2021). This variation in color expression is associated with 2 regulatory regions near genes responsible for pterin (sepiapterin reductase [ SPR ]) and carotenoid (beta‐carotene oxygenase 2 [ BCO2 ]) metabolism (Andrade et al .…”
Section: Introductionmentioning
confidence: 99%